Differentiation between benign and malignant thyroid nodules using diffusion-weighted imaging, a 3-T MRI study - Aghaghazvini, Leila; Sharifian, Hashem; Yazdani, Nasrin; Hosseiny, Melina; Kooraki, Saina; Pirouzi, Pirouz; Ghadiri, Afsoon; Shakiba, Madjid; Kooraki, Soheil (Indian Journal of Radiology and Imaging, 2018)
Background: Preoperative differentiation of benign from malignant thyroid nodules remains a challenge. Aims: This study assessed the accuracy of diffusion-weighted imaging (DWI) for differentiation between benign and malignant thyroid nodules. Materials and Methods: Preoperative DWI was performed in patients with thyroid nodule by means of a 3-T scanner magnetic resonance imaging (MRI). Images were obtained at b value of 50, 500, and 1000 mm2/s to draw an ADC (apparent diffusion coefficient) map. Findings were compared with postoperative histopathologic results. Receiver operating characteristic curve was used to assess the accuracy of different cutoff points. Results: Forty-one thyroid nodules (26 benign and 15 malignant) were included in this study. None of static MRI parameters such as signal intensity, heterogeneity, and nodule border was useful to discriminate between benign and malignant lesions. Mean ADC value was (1.94 ± 0.54) × 10−3 mm2/s and (0.89 ± 0.29) × 10−3 mm2/s in benign and malignant nodules, respectively (P-value < 0.005). ADC value cutoff of 1 × 10−3 mm2/s yielded an accuracy, sensitivity, and specificity of 93%, 87%, and 96% to discriminate benign and malignant nodules. Conclusion: DWI is highly accurate for discrimination between benign and malignant thyroid nodules.
Keywords: Diffusion; nodule; thyroid